NUTRITIONAL STATUS AND NEW TUBERCULOSIS SUSPECTED INCIDENCE AMONG JUNIOR STUDENTS AT KEPUTIH PUBLIC HEALTH CENTER: Status Gizi dan Kejadian Dugaan Tuberculosis Baru pada Siswa Sekolah Menengah Pertama Puskesmas Keputih Surabaya - Thoriq Izza Nugrahedi, Fadel; Ghanynafi, Abdullah; Arge Wada, A A Arjun; Shofiya Novita Sari, Siti; Astutik, Erni (Jurnal Berkala Epidemiologi, 2024)
Background: Tuberculosis (TB) is an infectious disease caused by the Mycobacterium tuberculosis. The countries with the third highest TB cases worldwide are India, China, and Indonesia. A decrease in stamina will occur in a person suffering from tuberculosis. Purpose: This study was conducted to determine the relationship between nutritional status and suspected new TB cases in junior high school students in the working area of Puskesmas Keputih Surabaya. Methods: This study was conducted with a cross-sectional study design in the working area of Puskesmas Keputih in 2023. Secondary data was obtained from Keputih Health Centre in 2023. The research sample used a total sampling population. The association between nutritional status and suspected new TB cases in junior high school students was tested using the chi-square method. Results: A chi-square test was conducted on high school students and found no significant association between nutritional status (underweight and average weight) and TB screening or suspected new TB cases (PR = 0.68, p-value = 0.16). In addition, it was also found that there was no significant association between nutritional status (overweight and average weight) and TB screening or suspected new TB cases (PR = 1.01, p-value = 1.00). Conclusion: There was no significant association between nutritional status and the incidence of new suspected tuberculosis in junior high school students. This indicates that other risk factors also play an essential role in influencing a person's immune system.